The Regeni case and Italy's Mediterranean policy: a turning point?. Issue 3 (1st September 2016) - Colombo, Matteo; Varvelli, Arturo
ABSTRACT: The Regeni case has called into question the traditional Italian foreign policy in the Mediterranean, which has been based on a business-oriented approach and an overall friendly attitude towards the existing governments. Under the pressure of public opinion, Renzi's executive has been pushed to rethink its current relations to Egypt, traditionally a close partner of Italy, thus weakening the once strong economic, political, and security partnership. This decision has had consequences for the role of Italy in the Libyan crisis, where Egypt supports General Haftar in the East and Italy is the main sponsor of the National Unity Government in the West. The paper argues that the Regeni case had an impact on the overall Italian Mediterranean strategy in the short term. However, it also states that, given that the current transformation has not yet been followed by a radical rethink of the cornerstones of Italian policy in the area, it is unlikely that it will mark the beginning of a fundamental review of Rome's strategy in the Mediterranean region in the coming years.